INPUT, PROSES, OUTPUT PEMBUATAN MUSIK BUMPER: PADA PROGRAM ACARA KUIS PAKIS BALI DI BALI TV - Luthfiansyah, Muhammad Raihan Luthfiansyah; Wiyati, Wahyu Sri; Ardini, Ni Wayan (MELODIOUS : JOURNAL OF MUSIC, 2024)
Bumper is an opening animation in a television program, serving as a short animation to depict the identity of a show or institution. Every TV program typically features a bumper to showcase its identity. During the internship in the MBKM 2023 program at Bali TV, I had the opportunity to create bumper music for the quiz show "Kuis Pakis Bali." I am grateful for this opportunity as it allows me to channel my passion for music and apply the knowledge gained in previous semesters to craft the bumper music for the "Kuis Pakis Bali" program. The process involved several stages: introduction, observation, music creation, and mixing/mastering. The introduction stage involved discussing the music bumper with Bali TV. The observation stage included analyzing existing bumper videos to create the musical accompaniment. In the music creation stage, I began composing the music for the bumper. Lastly, in the mixing and mastering stage, I merged the video and music, refining the sound to achieve balance and a pleasant listening experience.